Critical Thinking and Problem Solving Skill Development: A Study in Malaysian Public Universities - Azreen Rodzalan, Shazaitul; Mohamed Saat, Maisarah; Suriani Mohd Arif, Lily (International Journal of Engineering and Technology, 2018)
One critical measure to be hired at the workplace is the ability to think critically in problem solving. As future human capital, university graduates are urged to meet with this expectation. Hence, taking this expectation into consideration, this study aims to examine students’ critical thinking and problem solving skill development before and after they undergoing the industrial training. The study also aims to examine whether the problem solving skill’s development is influenced by supervisors’ leadership styles. This study is longitudinal. A total of 1227 students and 485 students completed the pre survey and post survey respectively. The questionnaire used consists of items adapted from Belbin thinking roles and leadership items based on Multifactor Leadership Questionnaire (MLQ). Result revealed that there is a significant improvement in students’ critical thinking and problem solving skill after undergoing their industrial training. The findings of this study provide some practical and empirical implications.